The Effect of Independence, Task Complexity, Audit Experience, and Objectivity on Audit Judgment in Public Accounting Firm in Medan City - Yusnita Sari Sianipar; Sepayana Br Sitepu; Sylvia Setiawan; Enda Noviyanti Simorangkir; Dina Anggriani (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This research looks at how auditors' independence, job difficulty, audit experience, and fairness affect their ability to make good audit decisions in Medan City public accounting firms (KAP). It comes from the urgent need to maintain audit quality so that financial records stay honest and reliable, especially in the business world, which is getting harder and more complicated all the time. The goal is to find out how much these things really affect how audit decisions are made. The method used is quantitative, and it involves polling 60 inspectors from two registered KAPs in Medan. The theories are tested with multiple regression analysis. The results show that auditors' fairness and independence have a big, positive effect on their audit judgment (with p-values below 0.05). while task difficulty actually has a negative effect, and audit experience even strengthens the positive influences of the other factors. Ultimately, the study concludes that boosting auditor independence and objectivity is crucial for optimizing audit decisions. The recommendations for KAPs are to prioritize ethics training programs and the development of auditors' work experience.